The Reformation : a brief history - Appold, Kenneth G. 1965- (Malden, MA : Wiley-Blackwell, 2011)
"The Reformation: A Brief History is a succinct and engaging introduction to the origins and history of the Protestant Reformation. A rich overview of the Reformation, skillfully blending social, political, religious and theological dimensions A clearly and engagingly written narrative which draws on the latest and best scholarship Includes the history of the Reformation in Scandinavia and Eastern Europe, areas that are rarely covered in any detail The Reformation is placed in the context of the entire history of Christianity to draw out its origins, impetus, and legacy "--
"In 1517, the actions of a simple monk ushered in a period of unparalleled religious and political upheaval. The Reformation: A Brief History provides a succinct yet comprehensive introduction to this extraordinary period, showing how and why the Protestant Reformation arose and unfolded. In this rich account, the author skillfully blends social history, religious and theological ideas with economic and political factors. The description is well-rounded, drawing not just on the actions of the main characters, but also the experiences and ideas of ordinary people, the quest for social justice, and the conflicting approaches to Christian unity. The events of the Reformation are placed in the context of Christian history to offer a fuller understanding of the period. The result is a truly engaging narrative that shows the reader exactly what was at stake, and why, as the events unfurled. Accessible, lucid and based on the best of current research, this book offers readers a wonderful overview of one of the most critical periods in Western history"--
Includes bibliographical references and index.
Keywords: Reformation; RELIGION / History